WASH and Nutrition Synergies : The Case of Tunisia - Cuesta, Jose; Maratou-Kolias, Laura (Taylor and Francis, 2019)
This paper develops a simple econometric strategy to operationalize the United Nations Children’s Fund’s (UNICEF’s) conceptual framework for nutrition. It estimates the extent to which child stunting correlates with investments in water, sanitation, and hygiene (WASH) across population groups (poor and non-poor) and residence (urban and rural). Moving away from estimating single intervention marginal returns, the empirical framework of intervention packages is tested in Tunisia, a country with notable but uneven progress in reducing stunting. A successful nutritional strategy will thereby require mapping the distinctive intervention packages by residence and socioeconomic status, away from universal policies, that more strongly correlate with reduction in stunting.